An Overview of Different Aspects of Commercial Farming - Deepak R Kasai , Devi Rdhadhika (International Journal of Modern Agriculture, 2021)
Commercial farming introduced in order to fulfill the demand of the food for society and it has different aspects. Commercial framing generally profit oriented. As population increases the demand of the food also increases but small scale farming can’t fulfill the requirement of large quantity of food for the society because it is usually done on small land farms. Commercial farming usually done on relatively big farm as compared to small scale farming and mostly utilizes machinery power for cultivation. Like other farming system, commercial farming also has some merits, demerits and challenges. This review paper discussed about the different aspects of commercial farming such as its characteristics, advantages, disadvantages, limitations and future scope of commercial farming. By addressing the challenges of the commercial farming, the quality of the food can be improved in the future because poor food quality is the major disadvantage of the commercial farming that has adverse effect on the health.